Filantropi Islam: A Systematic Literature Review - Zaenal Abidin; aan sugiharto (Talenta usu, 2026)
This study aims to explain the themes and topics of Islamic philanthropy studies, including clustering, networks, study areas, and dominant topics in Islamic philanthropy research. The research method applied in this study is a systematic literature review using 114 scientific articles sourced from the Scopus database, with article review conducted using the VOSviewer application. The findings reveal the trends, scope, and dominance of Islamic philanthropy studies, which have so far been largely related to economic aspects, Islamic economics, Islamic finance, Covid-19, charity, and waqf. The results of this study will contribute to the development of a research roadmap on Islamic philanthropy. Islamic philanthropy studies need more intensive attention because of their enormous potential, which has not yet been well consolidated in terms of either funds or programs, especially since religious motivation is a dominant factor for individuals to donate to Islamic philanthropic institutions. The limitation of this study is that the articles used were sourced only from the Scopus database, so the findings cannot comprehensively describe Islamic philanthropy around the world. Future research needs to use scientific articles sourced from other reputable international databases, such as Web of Science and Dimensions.